Statement by the Managing Director on the IMF's Crisis Response and Reform Agenda. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
Crisis response to date. As the world economy has become engulfed in the worst crisis in many generations, the Fund has mobilized on many fronts to support its member countries. We have responded with prompt, large and flexible financial support where needed. Our monitoring, forecasts, and policy advice, informed by a global perspective and by experience from previous crises, have been in high demand. We have deployed a broad financial safety net, through an overhaul of our general lending framework that makes it better suited to members' needs, and by garnering pledges for a massive increase in Fund resources. And we have contributed to the ongoing collective effort to draw lessons from the crisis for policy, regulation, and the global architecture.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Financing; Fund; Lending; PP; Quota Resource